2004
DOI: 10.1103/physreve.70.056218
|View full text |Cite
|
Sign up to set email alerts
|

Quantum computation of a complex system: The kicked Harper model

Abstract: The simulation of complex quantum systems on a quantum computer is studied, taking the kicked Harper model as an example. This well-studied system has a rich variety of dynamical behavior depending on parameters, displays interesting phenomena such as fractal spectra, mixed phase space, dynamical localization, anomalous diffusion, or partial delocalization, and can describe electrons in a magnetic field. Three different quantum algorithms are presented and analyzed, enabling to simulate efficiently the evoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…An application of DQS with a few qubits is the study of the dynamics of simple quantum maps (Georgeot, 2004;Levi and Georgeot, 2004;Schack, 1998;Terraneo et al, 2003). For instance, the quantum baker's map, a prototypical example in quantum chaos, has an efficient realization in terms of quantum gates (Schack, 1998).…”
Section: G Quantum Chaosmentioning
confidence: 99%
See 1 more Smart Citation
“…An application of DQS with a few qubits is the study of the dynamics of simple quantum maps (Georgeot, 2004;Levi and Georgeot, 2004;Schack, 1998;Terraneo et al, 2003). For instance, the quantum baker's map, a prototypical example in quantum chaos, has an efficient realization in terms of quantum gates (Schack, 1998).…”
Section: G Quantum Chaosmentioning
confidence: 99%
“…The quantum baker's map has been experimentally realized in NMR (Weinstein et al, 2002) and with linear optics (Howell and Yeaze, 2000). Another example is the kicked Harper model (Levi and Georgeot, 2004). It has been shown that in some cases the quantum approach to the kicked Harper model can provide a polynomial gain as compared to classical algorithms.…”
Section: G Quantum Chaosmentioning
confidence: 99%
“…Numerical simulations for increasing n s show a good precision for relatively low n s (Lévi and Georgeot 2004). The implementation of both e −iK cos(θ)/~a nd e −iL cos(~n)/~b y n s iterations of the appropriate M(α, U) needs 4 + 2(n q − a) + (n s − 1)(7 + 2(n q − a)) gates; the quantum Fourier transforms need n q (n q + 1) gates.…”
Section: Bertrand Georgeot 1232mentioning
confidence: 84%
“…The localization length in this regime becomes quickly larger than the system size for small number of qubits, thus allowing to explore the complexity of a chaotic wave function. Indeed, in the localized regime, the most important information resides not so much in such distributions, but in the localization properties, and their measurement on a quantum computer was already analyzed in [13,30].…”
Section: Quantum Phase Space Distributions For a Chaotic Quantum Mapmentioning
confidence: 99%
“…We focus on the phase space distribution (Wigner and Husimi functions) [10,11] These functions provide a two-dimensional picture of a one-dimensional wave function, and can be compared directly with classical phase space distributions. They have also been shown in [12,13] to be stable with respect to various quantum computer error models. Different phase space representation which can be implemented efficiently on a quantum computer will be explored, first the discrete Wigner transform, for which an original algorithm will be presented, and then a Husimilike transform, first introduced in this context in [14].…”
mentioning
confidence: 99%